Three-in-One Flesh: A Christian Reappraisal of Divorce in Light of Recent Studies - Rubio, Julie Hanlon (Journal of the Society of Christian Ethics, 2003)
The author argues that Christian theologians must consider the suffering of children in their moral evaluation of divorce. A review of recent social science literature shows the negative consequences of divorce, especially in low-conflict cases, and suggests the need to return to the tradition for retrieval of theologies of marriage that include children. In St. John Chrysostom, the author finds a three-in-one flesh metaphor that she claims is a more adequate description of marriage with children as lived reality. With the addition of parallel material from Vatican II and John Paul II, the author argues, it is possible to construct a new theology of marriage that moves beyond relationship to include commitments to spouses, children, and society.